Implementation of the Akad Murabahah Financing Program to Support SDGs: A Case Study at BMT Yaa Qawiyyu and BMT Sekawan Klaten - Maulana Elpraja Sami’ul Haq; Muthoifin; Daffa Ghifari (Profetika: Jurnal Studi Islam, 2024)
Objective: This study is to determine the implementation of the murabahah contract financing program at BMT Yaa Qawiyyu and BMT Sekawan Klaten and assess its suitability with the murabahah financing theory and fatwa of DSN MUI No. 04/DSN-MUI/IV/2000 regarding murabahah, while also supporting SDG Goal 8 and Goal 1 by encouraging inclusive, ethical, and sustainable financial access. Theoretical framework: The theoretical framework used is based on the theory of murabahah contracts in sharia economics and the provisions of sharia law formulated in the DSN MUI fatwa related to the mechanism for implementing murabahah contracts, which also aligns with global development agendas that promote responsible financial practices, as reflected in SDG Goal 16. Literature review: The literature review in this study covers theories about murabahah financing, implementation in Islamic financial institutions, and sharia regulations that regulate the practice, especially those issued by DSN MUI, emphasizing their role in achieving inclusive financial services as targeted in SDG Goal 10. Methods: The method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation of two research objects, namely BMT Yaa Qawiyyu and BMT Sekawan Klaten, and using primary and secondary data, providing contextual relevance to SDG Goal 17 through collaboration with community-based financial institutions. Results: The results of the study show that the implementation of the murabahah contract in the two BMTs is by the murabahah theory and the provisions of the fatwa of DSN MUI No. 04/DSN-MUI/IV/2000. BMT Yaa Qawiyyu implements a pure murabahah contract, where BMT buys goods first from suppliers, and then sells them to members at agreed prices and profits. In addition, the two BMTs also use the murabahah bil wakalah scheme, where BMT gives power of attorney to members to purchase goods on behalf of BMT, and after the purchase transaction is carried out, the murabahah contract process is carried out with an explanation of the price, profit, and payment terms. Implications: The implication of this study is the importance of understanding and proper application of the provisions of DSN MUI's fatwa in sharia financing operations to remain by sharia principles and provide transparency to customers, which contributes to financial inclusion and ethical financing as envisioned in SDG Goals 1, 8, and 16. Novelty: The novelty of this study lies in a specific case study of two BMTs that shows two models of the implementation of the murabahah contract.